IMPLEMENTASI PROFESIONALITAS GURU DALAM MENGINTEGRASIKAN TEKNOLOGI BERBASIS DIGITAL PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMA NEGERI 1 BONE KABUPATEN BONE BOLANGO - Tahaku, Nurwindi; Herson Anwar; Firmansah Kobandaha (An-Nahdlah: Jurnal Pendidikan Islam, 2025)
This study aims to describe and analyze the implementation of Islamic Religious Education (PAI) and Character Building (Culture) teacher professionalism in integrating digital-based technology at SMA Negeri 1 Bone line with the demands of the digital era, PAI teachers are expected to be able to utilize technology to improve the quality and attractiveness of learning. The focus of this study is to identify forms of teacher professionalism implementation in the use of technology, analyze the challenges faced, and describe the maximization efforts made to overcome these obstacles. This study uses a qualitative approach with a case study method. Data collection was carried out through observation, in-depth interviews with PAI teachers, and documentation. The collected data were analyzed descriptively to obtain a complete picture of the phenomenon under study. The study results show that the implementation of Islamic Religious Education teachers' professionalism in integrating technology has been very successful. Teachers creatively utilize various platforms such as Canva, Quizizz, Kahoot, in all stages of learning, from planning, implementation, to evaluation. However, this implementation faces significant external challenges, namely infrastructure limitations such as unstable internet connections and power outages, as well as student-driven challenges such as limited devices and the digital literacy gap.